Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Boalemo - Rivai, Sukariyati M; Saprudin, Saprudin; Junus, Onong; Masjhur, Mohamad Abdul Radjak; Hippy, Mega Nurannisa; Polapa, Lianti (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the influence of human resource (HR) competency, internal control systems, information technology (IT) utilization, and organizational commitment on the quality of local government financial reports in Boalemo Regency. The research is motivated by recuring findings from the Audit Board Of Indonesia (BPK)regarding financial report deficiencies across several local government agencies (OPDs), and the low rate of follow up on BPK recommendations. A quantitative method was employed using a survey approach involving 45 respondents from 15 OPDs in the Boalemo Regency Government. The results show that all four independent variables simultaneously affect the quality of financial reports. Partially, HR Competency, internal control systems, and IT utilization have a positive and significant effect, while organizational commitment doesnot have significant effect. These findings underscore the importance of strengthening financial reporting governance through improved HR Capacity, effective Internal Control System, and optimal use of technology.